Using homeopathica drugs combination at peripartal phase in preventing bovine subclinical mastitis (Faculty of Medicine Universitas Indonesia, 2004)
A total of 33 dairy lactating cows suffering from subclinical mastitis were classified into group A (10 cows), group B (12 cows) and group C (11 cows). They were treated with the combination of homeopathic drugs and placebo, applied at the 4th and 3rd week antepartum (a.p), and continuing every week postpartum (p.p), for four times. Group A received Coenzyme comp® (in the 4th and 3rd week a.p), Lachesis comp® combined with Traumeel®(1st and 2nd week p.p) and Coenzyme comp® combined with Carduus comp® (3rd and 4th week p.p). Group B received Traumeel®+ Mucosa comp® (4th and 3rd week a.p), Lachesis comp®+ Traumeel® (1st and 2nd week p.p) and Coenzyme comp®+ Carduus comp® (3rd and 4th week p.p) and group C as a placebo. The incidence of subclinical mastitis in group A and C appeared irregular. In contrast, group B showed a constant percentage (33.3%). Group A and B showed significant response to the homeopathic drugs, expressed as an increasing of the somatic cell count value. At peripartal phase, haptoglobin increased in group B 0.80 mg/ml and group A as well as placebo 1.40 mg/ml. After calving, group B expressed a constant value (0.05 mg/ml), while group A and placebo rose significantly. The milk yield in normal lactation period (the 3rd - 7th month) increased significantly, with an increasing 14.1% for group B and 4.9% A respectively. (Med J Indones 2004; 13: 221-6)